PENGARUH DESENTRALISASI DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJERIAL DENGAN KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN SEBAGAI INTERVENING - Adnantara, Komang Fridagustina (Jurnal Riset Akuntansi (JUARA), 2020)
The growing number of hotels has made management have to improve their performance to be able to compete. This study aims to examine the direct and indirect effects of decentralization and environmental uncertainty on managerial performance with the information characteristics of management accounting system as an intervening variable. The population in this study were starred hotels (1 to 5-star) in Denpasar. This study used respondents consisting of middle and lower level managers. 74 questionnaires were collected. The Data were tested using the path analysis model. The research results obtain (1) decentralization do not have a direct influence on the information characteristics of management accounting system, (2) environmental uncertainty have a direct influence on the information characteristics of management accounting system, (3) decentralization have a direct influence on managerial performance, (4) environmental uncertainty have no direct influence on managerial performance, (5) information characteristics of management accounting system have a direct influence on managerial performance, (6) information characteristics of management accounting system are not able to mediate the relationship between decentralization and managerial performance as intervening variables, but (7) information characteristics of management accounting system are able to mediate the relationship between environmental uncertainty and managerial performance as intervening variables.